Impact of MUC1 Expression on the Progression of Intraductal Papillary Mucinous Neoplasm With Worrisome Features During Follow-up. Issue 9 (October 2017) - Tomishima, Ko; Sai, Jin Kan; Kanazawa, Ryo; Miura, Hiroko; Shimizu, Ryo; Sato, Koki; Ishii, Shigeto; Saito, Hiroaki; Ito, Tomoyasu; Fukumura, Yuki; Shiina, Shuichiro; Watanabe, Sumio
Abstract : Objectives: The aim of this study was to investigate whether MUC1 expression is associated with progression of intraductal papillary mucinous neoplasms with worrisome features during follow-up. Methods: Fifteen patients positive for MUC1 and negative for MUC2 (MUC1 group) and 16 patients negative for MUC1 and MUC2 (control group) were followed up and examined for changes in diameters of the main and ectatic branches of pancreatic ducts, enlargement of mural nodules, and appearance of a solid mass, by imaging studies. All of them presented worrisome features, and none had "high-risk stigmata." Results: The sizes of the main and ectatic branches of pancreatic ducts increased in 8 (53.3%) and 8 (53.3%) patients, respectively, of the MUC1 group and in 1 (6.3%) and 1 (6.3%) patients, respectively, of the control group ( P = 0.0059 and 0.0059, respectively). A solid mass developed in 6 patients (33.3%) of the MUC1 group but in none of the control group patients ( P = 0.0373). Conclusions: Positive MUC1 expression in cell block cytology specimens may be associated with progressive dilation of the main and ectatic branches of pancreatic ducts and appearance of a solid mass in patients with intraductal papillary mucinous neoplasm with worrisome features during follow-up.